Dynamics of energy reserves and the cost of reproduction in female and male fiddler crabs - Delevati Colpo, Karine (2018)
The physiological costs of reproduction can be measured as the energy allocated to reproductive activities. In fiddler crabs, females allocate energy to vitellogenesis and brooding, whereas males perform expensive courtship behaviors. We evaluated in a large-scale study the reproduction cost of females and males of Leptuca uruguayensis in a temperate estuary, where their reproductive efforts are synchronized in a short reproductive season. The reproductive investments (vitellogenesis, spermatophore production, and male reproductive behaviors) were measured and related to the dynamics of storage and expenditure of energy reserves (glycogen, total lipids, and total protein) in the hepatopancreas, ovary, and muscle of the enlarged cheliped, throughout one annual cycle. Maximum energy storage occurred in winter, a period of low activity, whereas minimum energy storage occurred during the reproductive period, characterized by expensive activities. The glycogen reserves of the hepatopancreas decreased about 66% in females and 61% in males, suggesting high and similar physiological costs of reproduction between sexes, despite their different reproductive strategies to maximize their fitness.